Hemoglobin, Albumin, Lymphocyte and Platelet Score as a Novel Predictor of Mortality and Rebleeding in Patients with Upper Gastrointestinal Bleeding - Azapoğlu Kaymak B; Eksioglu M; Cimilli Öztürk T; Köroğlu M (International Journal of General Medicine)
Burcu Azapoğlu Kaymak,1 Merve Eksioglu,1 Tuba Cimilli Öztürk,1 Mehmet Köroğlu2 1University of Health Sciences, Fatih Sultan Mehmet Education and Research Hospital, Department of Emergency Medicine, Istanbul, Turkey; 2University of Health Sciences, Fatih Sultan Mehmet Education and Research Hospital, Department of Gastroenterology, Istanbul, TurkeyCorrespondence: Burcu Azapoğlu Kaymak, University of Health Sciences Fatih Sultan Mehmet Education and Research Hospital Department of Emergency Medicine Atasehir-Istanbul, Istanbul, Turkey, Email burcuazapkaymak@gmail.comPurpose: Upper gastrointestinal bleeding (UGIB) poses significant risks of morbidity and mortality, necessitating effective risk stratification tools. Traditional scoring systems such as the Rockall (RS), Glasgow-Blatchford (GBS), and AIMS65 have limitations in accurately predicting mortality and rebleeding. The Hemoglobin, Albumin, Lymphocyte, Platelet (HALP) score, initially developed for cancer prognosis, has demonstrated prognostic value in various conditions. This study aims to evaluate whether the HALP score, when assessed at admission, aligns with the Rockall score and can be used to predict rebleeding and 30- day mortality in UGIB patients.Patients and Methods: This retrospective study included 256 patients with confirmed UGIB admitted to a tertiary hospital in Istanbul, Turkey, between 2017 and 2024. Patient data, including demographics, vital signs, laboratory parameters, endoscopic findings, and clinical outcomes, were collected. The HALP score was calculated at admission to the emergency department. ROC curve analysis assessed the predictive accuracy of the HALP score for 30-day mortality, rebleeding, and its performance was compared with the Rockall score.Results: The predictive performance of the HALP and Rockall scores for 30-day mortality and rebleeding was evaluated using ROC analysis, with AUC values of 0.772 (95% CI: 0.715– 0.822) and 0.770 (95% CI: 0.714– 0.820) for mortality prediction, respectively (p = 0.9801). For rebleeding prediction, the Rockall score had a higher AUC (0.739, 95% CI: 0.681– 0.792) than the HALP score (0.688, 95% CI: 0.627– 0.744), though the difference was not statistically significant (p = 0.2969).Conclusion: The results of this study demonstrate that the HALP score can be used for prognosis prediction in UGIB, exhibiting comparable sensitivity and specificity to the Rockall score. Its ease of calculation using routine laboratory parameters offers a practical complement to existing scoring systems.Keywords: upper gastrointestinal bleeding, HALP score, prognostic scoring, mortality prediction